PERFORMANCE AND PARTICIPATION IN MUSLIM FORUMS IN MEDAN CITY: AN ANTHROPOLINGUISTICS PERSPECTIVE - Rezky Khoirina Tarihoran; Tasnim Lubis; Ratna Sari Dewi; Vera Kristiana; Ayu Melati Ningsih (IKIP Siliwangi, 2024)
The objective of this study is to ascertain the types of participation exhibited by individuals engaged in a Muslim forum, specifically presenters, speakers/ustadz, and residents as participants of the forum. The primary objective of this study is to identify performance trends within the Muslim forum process through the application of an anthropolinguistic methodology. The observed patterns of involvement can be elucidated by examining the phenomena of speaking activity within the context of the Muslim forum process. The primary sources of data utilized in this study consist of video recordings, interviews, and observations. The present study employs a descriptive qualitative research design. The findings of this study demonstrate that the presenter's performance include the initiation, conclusion, and facilitation of the event. The primary function of the speaker is to provide a lecture and provide guidance. The performance of the inhabitants includes the act of posing inquiries, providing answers, and reacting to both questions and jokes presented by the speaker. The Muslim forum primarily facilitates a lecture-based form of participation, characterized by limited interaction between participants throughout the lecture sessions.